Angle measurement accuracy assessment using inertial sensors in threedimensional coordinate system - Miziołek, Mateusz (Journal of Computer Sciences Institute, 2019)
This article discusses angle measurement accuracy assessment using inertial sensors in three-dimensional coordinate system. Vicon’s acquisition system was used as a reference system. The article describes conduct of the study and application that was used for collecting data from the smartphone. The article also contains methods, formulas and algorithms that were used to compare obtained data.